Hydrogeochemical study of surface waters from Araxá city, Minas Gerais State, Brazil - Bonotto, Daniel Marcos [UNESP] (Elsevier, 2020)
Barreiro area at Araxá city, Minas Gerais State, Brazil, has been well-known since the 19th century when started the studies of the healing properties for the tuberculosis treatment of the natural mineral waters of the springs Dona Beja (DBS) and Andrade Júnior (AJS). In addition, extensive mining activities devoted to the niobum and phosphate fertilizer exploitation have been developed there since the 60's and 70's by different companies, favoring the release of contaminants into the hydric resources of that environment. This paper reports a hydrogeochemical study of surface waters occurring at Barreiro area, comparing their major hydrochemical characteristics with those of other surface waters and rainwater occurring there for identifying possible degradation of their quality due to the anthropogenic inputs associated to the mining activities. The systematic utilized in this approach consisted on the adoption of various experimental steps: hydrochemical analysis by different methods of the several samples collected; hydrochemical data treatment and plotting using traditional statistical tests and geochemical diagrams; use of geochemical data in various sections of six sediment core for calculating the Geoaccumulation Index (Igeo) taking into account sediments outside of Barreiro area for yielding background values, as well as the concentrations reported in the literature for shales and NASC (North American shale composite); leaching experiments of sediment aliquots at room temperature (~20 °C) during about 24 h and using distilled water equilibrated with the atmosphere as leachant for the analysis of the release of barium, chloride, sulfate, phosphate and nitrate. All these protocols allowed an integrated evaluation of the constituents transport at Barreiro area and nearby, improving the knowledge of the environmental impacts associated to the mining activities developed there, responsible by a production of about 20,000 tons/year of ground apatite for phosphate use in agriculture and circa 936 billion metric tons of Nb2O5 ore.
Keywords: Araxá city; Barreiro area; Geoaccumulation Index; Leaching experiments; Niobium and phosphate exploitation; Surface waters hydrochemistry